Evaluation of ‘learning’ as a main thrust in transferor‐transferee relationships: small satellite technology transfer collaborative projects between developed and developing countries ‐ the case of Algeria - Ayad, Ahmed; Darby, Roger; Matthews, Ron (Intellect, 2021)
This article focuses on the transferor‐transferee relationship in the context of technology transfer collaborative projects between developed and developing countries. The case of the Algerian satellite industry, which utilized three small satellite collaborative projects with foreign companies over twenty years in order to acquire technology from abroad, has been used as an empirical study. The study evaluates transferor‐transferee relationships when small satellite collaborative projects are used as a technology transfer mechanism. It assesses whether technology transfer effectiveness or ‘learning’ is mutually understood by the two key transferor and transferee actors. It identifies a potential schism when transferor motives are often economic (business-oriented) whilst transferee motives are non-economic, aiming to learn and develop local capabilities for national developmental objectives. The study reveals that this initial non-alignment of objectives led to the adoption of a transfer mechanism where learning is not the main thrust. The principal finding extrapolated from this research is that this inadequacy is rooted in the fact that Algerians had not clearly dissociated the objective of ‘satellite technological learning’ from that of ‘satellite applications’. Recommendations for future research include the need to clearly prioritize the objective of ‘technological learning’ to avoid confusion as to the transfer mechanisms to adopt.
Keywords: developing countries; knowledge management; satellite technological learning; small satellite collaborative projects; technology transfer; technology transfer effectiveness; transferor‐transferee relationships